A Bibliometric Analysis of Translation Studies in Indonesia: Mapping Trends and Research Trajectories - Novriyanto Napu; Usman Pakaya; Hanisah Hanafi; Moon Hidayati Otoluwa; Amirullah Abduh (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Background: Translation Studies has expanded internationally through bibliometric, computational, and interdisciplinary developments, yet the publication trajectory of Translation Studies in Indonesia has not been mapped systematically. A bibliometric overview is therefore needed to identify the field’s thematic concentration, collaboration patterns, and publication visibility. Methodology: This study employed a bibliometric design using records retrieved from Scopus and selected Indonesian peer-reviewed journals published between 2014 and 2025. After eligibility filtering, 137 Indonesia-focused records and 7,113 international reference records were analyzed using Biblioshiny. Findings: Indonesian Translation Studies was dominated by humanistic, pedagogical, and culturally oriented themes, whereas corpus-based, computational, and machine-translation topics appeared less frequently. In contextual comparison with the international reference set, the Indonesian corpus showed slower thematic diversification and lower visibility of technology-oriented translation research. Conclusion: These findings indicate that Indonesian Translation Studies is growing, but its publication profile remains more concentrated in humanistic and pedagogical domains than in technology-oriented and corpus-based areas. This pattern matters because it influences how the field may engage with emerging methods, international collaboration, and wider scholarly visibility in contemporary Translation Studies. Originality: This study provides a bibliometric mapping of Indonesian Translation Studies based on peer-reviewed publication records and situates the national corpus in contextual comparison with an international reference set.